DECOLONIZING NEWSMAKING ON YOUTUBE: THE CASE OF CLIMATE JOURNALISM DURING THE COP26 SUMMIT - Ritter, Christian; Goel, Rahul; Sharma, Rajesh (AoIR Selected Papers of Internet Research, 2023)
This paper examines the role of newsmaking on the digital platform YouTube during the 2021 Climate Change Summit. Drawing on data collected with the software NodeXL Pro, we assess the connected communities, authorities, and popularity within a YouTube comment network. The data set of the investigation was assembled by the query ’COP26’. Drawing on the measures of influence in-degree, out-degree and PageRank, were ranked the YouTube channels of the researched network. In addition, the layout algorithm Force Atlas 2 was employed to detect network clusters in the software program Gephi. Finally, the study drew on Natural Language Processing to analyze the comment corpus. Our key findings suggest that YouTube channels of well-established, professional news corporations, such as BBC News, DWNews, and Sky News, reached high scores for the PageRank analysis. Based on the evidence collected, we argue that professional news corporations acted as influencers during the coverage of the 2021 Climate Summit on YouTube. This investigation contributes to understanding the role of digital platforms in the science communication on climate change and the negotiations of (post)colonial pasts. Its findings imply that claims for climate justice are increasingly played out within a diverse, global transmedia ecology. Climate justice is increasingly intertwined with decolonial voices.